ANALISIS SENTIMEN SELL IN MAY AND GO AWAY PADA SAHAM TERINDEKS LQ45 PERIODE 2020-2021 - Versiandika Yudha Pratama (PROSEDING, 2022)
Investors sometimes refer to circulating information and analyst recommendations when investing their assets, so that stock prices in the market generally reflect all available information. However, sometimes stock prices do not reflect available information or commonly known as market anomalies. The anomaly that will be discussed in this study is part of the seasonal anomaly, namely Sell in May and Go Away (SMGA), investors believe that stock returns for the May-October period tend to be lower than November-April. This study aims to determine the SMGA sentiment that occurs in LQ45 indexed stock returns for the 2020 and 2021 periods. And, this type of research is classified as an event study with the sample being the monthly return of LQ45 indexed stocks for the 2020 and 2021 periods, with data analysis technique used statistical analysis, including the normality test and the paired sample t-test if the data was normally distributed or the Wilcoxon signed rank test if the data were not normally distributed. The results showed that there was no significant difference between LQ45 stock returns for the 2020 and 2021 periods in May-October and November-April. In other words, the SMGA sentiment (May-October) in the 2020 and 2021 periods did not show any difference in returns compared to the NonSMGA period (November-April). Keywords: Sell in May and Go Away, Return, LQ45 Index